Cayagzi (Riva) Basin Natural Environmental Conditions (Geological-Geomorphological-Hydrographic Perspective) and Impact on Sustainable Use - (:unkn) unknown (MARMARA UNIV, 2015)
Located on Cayagzi Kocaeli Plateau (Riva) basin has a catchment area of approximately 859 km(2) like (Figure 1). Geological, geomorphologic sense, forming a basin unit area, also meet one of the major watersheds in Istanbul. Basin, which drains Cayagzi (Riva) River, in southeastern stemming from Kocaeli Province territory, in the north Cayagzi (Riva) is poured into the Black Sea near the Cayagzi (Riva) village. The middle section of the settled Omerli Reservoir Watershed, including primarily Aanadol Collar, Istanbul meets the water needs of the city. Basin today and in the future in a sustainable way for the use of the opportunities offered by the natural conditions and the analysis of risk is important. In this regard, the geological context; use of facilities identified with tectonic lithologic potential threats and risks need to be assessed in this area. Also the problems of the geomorphological potential (slope, landslides, etc.) to determine together and to take precautions, the detection of the presence of water, to be managed by maintaining the quality, examining the risk of flood-slant and floods and solutions to produce important.
Keywords: Cayagzi (Riva) Basin; Istanbul; watershed; Omerli; geological features; geomorphological features; hydrographic features; sustainable use